Preoperative Prognostic Nutritional Index Predict Survival in Patients With Resectable Esophageal Squamous Cell Carcinoma - Zheng, Zhiwei; Zhu, Huide; Cai, Hongfu (Frontiers in Nutrition, 2022)
Background Prognostic nutritional index (PNI) is one of the most important factors related to prognosis in many types of cancer. This study aimed to evaluate the PNI on predicting the overall survival (OS) in resectable esophageal squamous cell carcinoma (ESCC). Methods A total of 165 patients with resectable ESCC were included in our retrospective study. PNI values before surgery were calculated for each patient [PNI = 10 × albumin (gr/dL) + 0.005 × total lymphocyte count (mm3)]. PNI cutoff value was selected by drawing receiver operating characteristics (ROC) curve, which used OS time as the endpoint. The Kaplan-Meier method and the Cox regression model of multivariate analysis were used to analyze the prognostic relationship between PNI and OS. Results Among the 165 patients, 34 (20.6%) were women and 131 (79.4%) were men. The mean age was 62.67 ± 7.95 years, with the age range from 44 to 85 years. The average PNI was 46.68 ± 8.66. ROC curve showed that the best cutoff value was 43.85. All patients were divided into two groups: 72 patients (43.6%) were in the low PNI group (<43.85), while 93 patients (56.4%) were in the high PNI group (≥ 43.85). Univariate analysis demonstrated that PNI, tumor length, and T-stage and pathological stage were related to the prognosis of patients with ESCC (P <0.05). The Kaplan-Meier curve showed that the high PNI group has significantly increased OS compared to low PNI group (p = 0.01). Three-year OS rates were 57.5% in the low PNI group while 77.7% in the high PNI group. Univariate analysis showed that advanced pathological stage, large tumor length, and low PNI (separately, p < 0.05) were significant risk factors for shorter OS. Multivariate analysis showed that tumor length (P = 0.008) and PNI (P = 0.017) were independent prognostic factors in patients with resectable ESCC. Conclusion PNI is a simple and useful predictive marker for the OS time in patients with radical esophagectomy.